Knowledge and Participation of Male Partners in Antenatal Care attending Antenatal Clinics in Birat Medical College Teaching Hospital - Pradhan, Tarun; Dahal, Prerana; Dhamala, Jiba Nath; Yadav, Siddartha Kumar; Rathi, Nikita; Rauniyar, Zenith (Birat Journal of Health Sciences, 2022)
Introduction: Male partner participation and being prepared of complications and delivery during pregnancy is extremely important for successful pregnancy outcome. Objective: Objective of this study was to assess Knowledge and participation of male partners in antenatal care attending antenatal clinics at Birat Medical College Teaching Hospital. Methodology: A cross-sectional prospective study was done in Department of Obstetrics and Gynecology, BMCTH. Male partners accompanying primigravid pregnant lady were included. 150 male partners were included for the study. Knowledge of male partners were assessed using pre-tested questionnaire and the knowledge was scored for poor, average and good. Frequency and percentage were calculated for sociodemographic variables and male partner knowledge questionnaire. Result: Majority of male partners accompanying wife were educated (96%) and skilled (81.3%). 89.3% were between 20-35 years. Both couples involved in decision making were 48.7% and 85.3% had planned pregnancy. 89.3% had good knowledge about importance of antenatal care, pregnancy complications and delivery preparedness. Knowledge of pregnancy related complication among male partners were significantly related to level of education, age of partner, employed and skilled partner and couple with planned pregnancy. Knowledge of delivery preparedness was significantly related to male partner education, occupation and if couple are making decision in family. Knowledge score of male partners showed significant relation with level of education, involvement in skilled occupations, involvement of couple in decision making. Conclusion: Knowledge of male partners involved in antenatal care with pregnant lady showed good knowledge of antenatal care events, pregnancy related complication and also showed positive importance of hospital delivery.